The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1754-6834-6-128
|View full text |Cite
|
Sign up to set email alerts
|

Engineering E. coli strain for conversion of short chain fatty acids to bioalcohols

Abstract: BackgroundRecent progress in production of various biofuel precursors and molecules, such as fatty acids, alcohols and alka(e)nes, is a significant step forward for replacing the fossil fuels with renewable fuels. A two-step process, where fatty acids from sugars are produced in the first step and then converted to corresponding biofuel molecules in the second step, seems more viable and attractive at this stage. We have engineered an Escherichia coli strain to take care of the second step for converting short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
(31 reference statements)
1
13
0
Order By: Relevance
“…Most recently, one study has reported an engineered E. coli that carries a synthetic pathway consisting of Clostridium buk, ptb, and adhE2 for n-butanol production from butyrate (Mattam and Yazdani, 2013). Under the controlled fermenter condition, their E. coli strain grown on TB rich medium produces 1.85 g/L (25 mM) n-butanol from glycerol (5 g/L) and butyrate (2.2 g/L) at 100 h. To improve the production, a high cell density of the strain is used and the n-butanol titer reaches 4.4 g/L (60 mM) with consumption of 5.3 g/L butyrate at 24 h. In addition, there is around 4 g/L acetate production.…”
Section: N-butanol Production By Glucose and Butyrate Feedingmentioning
confidence: 99%
“…Most recently, one study has reported an engineered E. coli that carries a synthetic pathway consisting of Clostridium buk, ptb, and adhE2 for n-butanol production from butyrate (Mattam and Yazdani, 2013). Under the controlled fermenter condition, their E. coli strain grown on TB rich medium produces 1.85 g/L (25 mM) n-butanol from glycerol (5 g/L) and butyrate (2.2 g/L) at 100 h. To improve the production, a high cell density of the strain is used and the n-butanol titer reaches 4.4 g/L (60 mM) with consumption of 5.3 g/L butyrate at 24 h. In addition, there is around 4 g/L acetate production.…”
Section: N-butanol Production By Glucose and Butyrate Feedingmentioning
confidence: 99%
“…In another study, the butyrate-conversion strain (BUT-3EA) of E. coli was engineered by deleting ldhA, adhE, frdA, and pta genes and inserting native atoDA, acs and Clostridium adhE2 genes. The recombinant strain (BuT-3EA) was able to accumulate a titer of 6.2 g/L of 1-butanol using glucose and butyrate as a carbon sources [39], the titers were 1.5fold higher than the previously engineered strain using glycerol and butyrate as carbon sources [104].…”
Section: Elimination Of the Competitive Pathwaysmentioning
confidence: 99%
“…The zwf gene was amplified from E. coli DH5α genomic DNA and cloned in the pZS21mcs plasmid at KpnI and HindIII restriction sites to generate the pZF23 plasmid. Gene deletions in DH5α were achieved through the P1 transduction method (Fatma et al, 2016;Mattam and Yazdani, 2013;Munjal et al, 2012). The phage lysate was prepared and enriched by using the single gene knockout strain obtained from CGSC, and the targeted gene was replaced by an FRT flanked-kanamycin resistance cassette.…”
Section: Strain and Plasmid Constructionmentioning
confidence: 99%
“…Validation of the in silico findings required selection of a suitable E. coli host strain as the genetic background of the host makes a significant impact on the metabolite profiles (Liu et al, 2014;Mattam and Yazdani, 2013;Song et al, 2016). Therefore we compared hydrocarbon profiles in eight different E. coli strains, i.e., E. coli B, DH5α, M15, MG1655, BW25113, Top10, BL21, and JM109, by transforming them with plasmid pZS22 and found that DH5α showed the highest alkane production ( Fig.…”
Section: Implementation Of In Silico Finding Under In Vivo Conditionsmentioning
confidence: 99%
See 1 more Smart Citation